The Impact of TikTok-Based Health Education on High School Students’ Knowledge of HIV/AIDS - Mustika Budiarti, Baiq; Wahyudi, Iwan; Fitrihan Rukmana, Baiq (Balai Publikasi Indonesia, 2025)
HIV/AIDS is a disease that can cause a person's immune system to decline to the point of death. HIV/AIDS in adolescents is an important problem to pay attention to, considering the many behavioral problems adolescents are increasingly vulnerable to HIV/AIDS. The large number of HIV/AIDS cases among adolescents is caused by low adolescent knowledge. This study was conducted to determine the effect of TikTok-based health education on adolescents' knowledge about HIV/AIDS at SMA Negeri 2 Jonggat. The method used in this study is contingent with a pre-experimental design using the one group pre – test – post – test approach. The number of respondents in this study is 40 people, with purposive sampling technique. The results of the Wilcoxon rank test showed a P-value of 0.001 < 0.05 which means that there is an influence of TikTok-based health education on adolescents' knowledge about HIV/AIDS at SMA Negeri 2 Jonggat, it can be concluded that TikTok-based health education has a significant influence on adolescents’ knowledge about HIV/AIDS.